Permeation enhancer dodecyl 6-(dimethylamino)hexanoate increases transdermal and topical delivery of adefovir: influence of pH, ion-pairing and skin species - Vávrová, Kateřina; Lorencová, Kateřina; Novotný, Jakub; Holý, Antonín; Hrabálek, Alexandr (European journal of pharmaceutics and biopharmaceutics, 2008)
Adefovir (9-(2-phosphonomethoxyethyl)adenine) is an acyclic nucleoside phosphonate currently used for the treatment of hepatitis B. The aim of this study was to evaluate the effect of permeation enhancer DDAK (6-dimethylaminohexanoic acid dodecyl ester) on the transdermal and topical delivery of adefovir. In porcine skin, DDAK enhanced adefovir flux 42 times with maximum at pH 5.8 suggesting ion pair formation. DDAK increased thermodynamic activity and stratum corneum/vehicle distribution coefficient of adefovir, as well as it directly decreased the skin barrier resistance. Maximal flux was observed already at 2% adefovir+1% DDAK. The results were confirmed in freshly excised human skin where DDAK enhanced adefovir flux 179 times to 8.9 microg/cm(2)/h. This rate of percutaneous absorption would allow for reaching effective plasma concentrations. After the topical application, adefovir concentrated in the stratum corneum with low penetration into the deeper skin layers from either aqueous or isopropyl myristate vehicle without the enhancer. With 1% DDAK, adefovir concentrations in the viable epidermis and dermis were 33-61 times higher. These results offer an attractive alternative to established routes of administration of adefovir and other acyclic nucleoside phosphonates.
Keywords: farmaceutická chemie; Animals; Antiviral Agents; Female; difuzní komory kultivační; Caproates; Kinetics; Hydrogen-Ion Concentration; Adenine; antivirové látky; ženské pohlaví; druhová specificita; Methylamines; aplikace kožní; Skin Absorption; lidé; Chemistry, Pharmaceutical; Administration, Cutaneous; Species Specificity; prasata; kůže; kožní absorpce; farmaceutická vehikula; Pharmaceutical Vehicles; kapronáty; Diffusion Chambers, Culture; organofosfonáty; adenin; Skin; Swine; methylaminy; permeabilita; Permeability; zvířata; koncentrace vodíkových iontů; kinetika; Organophosphonates; Humans